The effect of past defaunation on ranges, niches, and future biodiversity forecasts - Sales, Lilian P.; Galetti, Mauro [UNESP]; Carnaval, Ana; Monsarrat, Sophie; Svenning, Jens-Christian; Pires, Mathias M. (Wiley, 2022)
Humans have reshaped the distribution of biodiversity across the globe, extirpating species from regions otherwise suitable and restricting populations to a subset of their original ranges. Here, we ask if anthropogenic range contractions since the Late Pleistocene led to an under-representation of the realized niches for megafauna, an emblematic group of taxa often targeted for restoration actions. Using reconstructions of past geographic distributions (i.e., natural ranges) for 146 extant terrestrial large-bodied (>44 kg) mammals, we estimate their climatic niches as if they had retained their original distributions and evaluate their observed niche dynamics. We found that range contractions led to a sizeable under-representation of the realized niches of several species (i.e., niche unfilling). For 29 species, more than 10% of the environmental space once seen in their natural ranges has been lost due to anthropogenic activity, with at least 12 species undergoing reductions of more than 50% of their realized niches. Eighteen species may now be confined to low-suitability locations, where fitness and abundance are likely diminished; we consider these taxa 'climatic refugees'. For those species, conservation strategies supported by current ranges risk being misguided if current, suboptimal habitats are considered baseline for future restoration actions. Because most climate-based biodiversity forecasts rely exclusively on current occurrence records, we went on to test the effect of neglecting historical information on estimates of species’ potential distribution – as a proxy of sensitivity to climate change. We found that niche unfilling driven by past range contraction leads to an overestimation of sensitivity to future climatic change, resulting in 50% higher rates of global extinction, and underestimating the potential for megafauna conservation and restoration under future climate change. In conclusion, range contractions since the Late Pleistocene have also left imprints on megafauna realized climatic niches. Therefore, niche truncation driven by defaunation can directly affect climate and habitat-based conservation strategies.
Keywords: biodiversity conservation; defaunation; ecological niche models; refugee species; shifting baselines